Strengths and Challenges of Secretory Ribonucleases as AntiTumor Agents - Jessica Castro; Marc Ribó; Maria Vilanova; Antoni Benito (MDPI AG, 2021)
Approaches to develop effective drugs to kill cancer cells are mainly focused either on the improvement of the currently used chemotherapeutics or on the development of targeted therapies aimed at the selective destruction of cancer cells by steering specific molecules and/or enhancing the immune response. The former strategy is limited by its genotoxicity and severe side effects, while the second one is not always effective due to tumor cell heterogeneity and variability of targets in cancer cells. Between these two strategies, several approaches target different types of RNA in tumor cells. RNA degradation alters gene expression at different levels inducing cell death. However, unlike DNA targeting, it is a pleotropic but a non-genotoxic process. Among the ways to destroy RNA, we find the use of ribonucleases with antitumor properties. In the last few years, there has been a significant progress in the understanding of the mechanism by which these enzymes kill cancer cells and in the development of more effective variants. All the approaches seek to maintain the requirements of the ribonucleases to be specifically cytotoxic for tumor cells. These requirements start with the competence of the enzymes to interact with the cell membrane, a process that is critical for their internalization and selectivity for tumor cells and continue with the downstream effects mainly relying on changes in the RNA molecular profile, which are not only due to the ribonucleolytic activity of these enzymes. Although the great improvements achieved in the antitumor activity by designing new ribonuclease variants, some drawbacks still need to be addressed. In the present review, we will focus on the known mechanisms used by ribonucleases to kill cancer cells and on recent strategies to solve the shortcomings that they show as antitumor agents, mainly their pharmacokinetics.